IMPLEMENTASI KEBIJAKAN PEMUNGUTAN PAJAK HOTEL DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN SEMARANG - Anggun Yusti Indarsari; Ida Hayu Dwimawanti; Aloysius Rengga (Journal of Public Policy and Management Review, 2013)
Regards Semarang regency otonimi goes to remind PADnya claimed by the lessor in the county, one of which is a Lease Hotel. Underlying regulations Lease Hotel exercise that is PERDA no. 10 of 2010 on Regional Taxes. Performance problems are namely RAS in 2012 fell in comparable estimates the 2011 budget year. And where this lease for 3 years in a row unrealized suitable targets have to be determined. These researchers describe/describe the implementation of the Tax PERDA Hotel in Semarang District and any factors that support the implementation of policy outcomes mentioned.According to George Edward III, supported by communications policy implementation, resource, dispositions and organizational structure. In this study the factors that support the implementation of Semarang regency hotel tax that is communication, disposisi. research resources is a description of the types of qualitative research. Informants obtained by using purposive sampling (sampling intended) that informants who know well the problems of implementing the Hotel Tax. The informant was the head lease areas, - after the data perolah, then tersenbut data analyzed through the stages of data reduction, data presentation and then verify.Result decision showed that the implementation of the Tax PERDA Regency Hotel in Semarang not going well, it is evident from PAD achievement in 2012 decreased, the apparatus is not clear communication, inadequate human resources (number, capacity, facilities), and attitudes about friendly.Finally apparatus recommendations from researchers are socialized in intersif to add taxpayer resources (number, capacity, facilities) are available, and provide specialized training related to service to the taxpayer.